Emerging Methods for Oil Extraction from Food Processing Waste - Prakash, Prem (Florida CRC Press, 2025)
Emerging Methods for Oil Extraction from Food Processing Waste is a comprehensive and cutting-edge exploration of sustainable oil extraction practices, catering to professionals and researchers in food science. The book, spanning 13 insightful chapters, intricately reviews the extraction of oil from food processing by-products, including pomace and surplus raw materials. It specifically focuses on emerging non-thermal technologies, offering valuable insights into improving oil extraction rates. The discussions encompass factors influencing extraction rates and suggest processing conditions based on various extraction methods and raw materials. In addition to providing a nuanced understanding of conventional and novel extraction techniques, the text delves into the diverse applications of the extracted oil, ranging from food preservation to fortification and fat replacement. Notably, it covers advanced processing techniques for enhancing oil stability, bioavailability, and bioactivity through emulsion and encapsulation methods. Addressing crucial commercial aspects, the text explores economic feasibility, safety considerations, and consumer acceptability, providing a holistic perspective for successful industrial adaptation. Authored by global specialists, each chapter offers in-depth scientific reports and critical analyses, making this volume an indispensable resource for continuous research and advancement in the dynamic field of food processing.
Keywords: Oils and fats Extraction (Chemistry)--Methodology